Psychometric properties of the Swedish version of the Patient Health Questionnaire-9: an investigation using Rasch analysis and confirmatory factor analysis - David Forsström; Farzaneh Badinlou; Magnus Johansson; Olivia Ojala; Samir El Alaoui; Kristoffer N. T. Månsson; Alexander Rozental; Johan Lundin; Simon Jangard; Shervin Shahnavaz; Karolina Sörman; Nitya Jayaram-Lindström; et al. (BMC Psychiatry)
Abstract Depression is one of the most common psychiatric conditions. Given its high prevalence and disease burden, accurate diagnostic procedures and valid instruments are warranted to identify those in need of treatment. The Patient Health Questionnaire-9 (PHQ-9) is one of the most widely used self-report measures of depression, and its validity and reliability has been evaluated in several languages. However, the Swedish translation has yet not been subject to psychometric evaluation, and no previous psychometric evaluation of the instrument have used both Rasch analysis and classic test theory. The aim of this study was to investigate validity and reliability of the PHQ-9 in a Swedish sample of individuals with self-reported current or past mental health problems using Rasch analysis and confirmatory factor analysis. A sample of 4958 participants was recruited from an online survey covering different aspects of covid-19 and mental health targeted towards individuals with mental health problems. Results showed that a one-factor solution fit the data after removing one item and that some items had a different response pattern for older respondents. Furthermore, after removing item 2 and merging the two middle response categories for item 9, the Swedish translation of PHQ-9 showed adequate psychometric properties. The findings suggests that the Swedish translation of PHQ-9 may need to be adapted in order to make adequate interpretations of an individual score and to differentiate between populations. Further tests of its validity and reliability in other Swedish samples are needed to fully understand the properties of the Swedish version of PHQ-9.